Preoperative chemoradiotherapy for esophageal or gastroesophageal junction cancer: results from a retrospective study using extended CROSS regimen - Tobias Haltmeier; Jennifer Brazerol; Yves Borbely; Elena Riggenbach; Anna Stenger-Weisser; Burim Sermaxhaj; Martin D. Berger; Hossein Hemmatazad (Radiation Oncology)
Abstract Background The standard of care for locally advanced esophageal cancer includes perioperative chemotherapy or neo-adjuvant chemo-radiotherapy (CRT), followed by surgery. At our institution, a modified neo-adjuvant regimen combining elements from CROSS and CALGB 9781 trials was adopted. This study aimed to assess the impact of our modified regimen on oncological outcomes, toxicity profile and pathological complete response rates compared to the CROSS trial. Methods This observational study included patients with esophageal cancer who underwent neo-adjuvant CRT followed by tumor resection at a tertiary care university hospital between 2014 and 2018. The modified radiation therapy consisted of 28 fractions of 1.8 Gy (50.4 Gy in total) with weekly carboplatin/paclitaxel. We assessed mortality over time using the median survival time. The impact of pathological complete response and radiation intensity on mortality was assessed in multivariable Cox regression analysis, adjusting for clinically relevant variables, including sex, age, American Society of Anesthesiologists (ASA) physical status classification system score, tumor and nodal stage, and the histological tumor type. Results A total of 46 patients were included. Median age was 67 years (IQR 9), 36 patients (78.3%) were male. An ASA score ≥ 3 was reported in 90.7% of the patients. Among the patients, 38 (82.6%) had a clinical tumor stage (cT) of ≥ 3, and 42 (91.3%) showed a positive endo-sonographic nodal stage (uN+). Pathological complete response was found in 7/42 patients (16.7%). Median survival time was 2.7 years (95% CI 1.340–4.084). In multivariable Cox regression analysis, pathological complete response was associated with significantly lower mortality over time (OR 0.152, 95%CI 0.049–0.989, p = 0.048). For larger radiation volumes, a trend towards increased mortality was shown, although not statistically significant (radiation volume/100: OR 1.172, 95%CI 0.987–1.392). Conclusions In patients with esophageal cancer undergoing trimodal therapy, the radiation dose escalation to 50.4 Gy was not associated with higher rates of pathological complete response or a survival benefit compared to the results of the CROSS trial. However, multivariable analysis revealed a trend toward increased mortality with larger radiation volumes. Based on these results, using modern radiotherapy techniques such as online adaptive radiotherapy might be more beneficial instead of escalating the radiation dose.